(untitled) (Research, Society and Development, 2023)
Cystic Fibrosis is an autosomal recessive genetic disease characterized by mutations in the CFTR gene (Cystic Fibrosis Transmembrane Conductance Regulator), responsible for chloride transport through the cell membrane. It causes alterations in the secretions of several organs, making them thick and coarse, besides causing several metabolic alterations in the human organism. In the state of Mato Grosso do Sul there are seventy people with Cystic Fibrosis being treated at the IPED APAE Institute in Campo Grande. Within this context, through a methodology of descriptive and observational study four pediatric volunteers who underwent gastrostomy were selected for data collection. These data were applied to laboratorial exams, anthropometric relations, and the Shwachman Scale method with the objective of evaluating the possible benefits that the gastrostomy (GT) can present in these patients with Cystic Fibrosis. After the insertion of the gastrostomy, it was possible to observe an improvement in the analyzed profiles and in the quality of life of each patient studied; therefore, it is noteworthy that studies in this field should be more widespread for a better statistical evaluation, thus increasing the sample for future studies.